Anxiety and depression affect pain drawings in cervical degenerative disc disease. (3rd April 2017) - MacDowall, Anna; Robinson, Yohan; Skeppholm, Martin; Olerud, Claes
Abstract: Introduction: Pain drawings have been frequently used in the preoperative evaluation of spine patients. Until now most investigations have focused on low back pain patients, even though pain drawings are used in neck pain patients as well. The aims of this study were to investigate the pain drawing and its association to preoperative demographics, psychological impairment, and pain intensity. Methods: We carried out a post hoc analysis of a randomized controlled trial, comparing cervical disc replacement to fusion for radiculopathy related to degenerative disc disease. Preoperatively the patients completed a pain drawing, the Hospital Anxiety and Depression Scale (HADS), and a visual analogue scale (VAS). The pain drawing was evaluated according to four established methods, now modified for cervical conditions. Comparisons were made between the pain drawing and age, sex, smoking, and employment status as well as HADS and VAS. Results: Included were 151 patients, mean age of 47 years, female/male: 78/73. Pain drawing results were not affected by age, sex, smoking, and employment status. Patients with non-neurogenic pain drawings according to the modified method by Ransford had higher points on HADS-anxiety, HADS-depression, and HADS-total. Patients with markings in the head region had higher score on HADS-depression. Markings in the neck and lower arm region were associated with high values of VAS-neck and VAS-arm. Conclusions: Pain drawings were affected by both pain intensity and anxiety/depression in cervical spine patients. Therefore, the pain drawing can be a useful tool when interpreting the patients' pain in correlation to psychological impairment and pain location.